Comparison of Pozzolanic Additives for Normal and High Strength Concrete - Justs, Janis; Shakhmenko, Genadij; Bajare, Diana; Toropovs, Nikolajs (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Microsilica is widely recognized as a “benchmark” for pozzolanic products. Although microsilica is an industrial byproduct, it has recently become very expensive. Four different pozzolanic additives were compared by the authors of this study. Two of the additives were commercially available products – microsilica by Elkem and Centrilit NC by MC Bauchemie. The other two additives were produced under laboratory conditions. Both of them were clay-based materials. Compressive strength was determined after 7, 28 and 155 days. The objective of this research was to determine alternatives to microsilica and evaluate pozzolanic additives performance in normal and high-strength concrete.